Women Glass Ceiling: Barriers and strategies - Vilvijaya, Indu Kochar (International Journal of Psychosocial Rehabilitation, 2020)
The main focus of the article is to review the barriers of glass ceiling in relation to women at all levels in corporate sector that hinder the overall progression of women toward the higher ladder in their career development and explore the strategies to overcome these barriers. Various strategies needs to be framed in the fields where she is still unrepresented. Affirmative actions and policies like quotas and reservations have been introduced. And these policies have certain opposition from the side of men. Initial study also indicates that women at higher educational levels are less likely to support the strategies that help to shatter this glass ceiling. The study found that there are multiple possible explanations for gender based discriminations.